The importance of the diurnal cycle of Aerosol Optical Depth in West Africa. Issue 4 (27th February 2013) - Kocha, C.; Tulet, P.; Lafore, J.‐P.; Flamant, C.
Abstract : [1] High resolution atmospheric simulations with the AROME model coupled with a dust module over West Africa for the whole of June 2006 were used to calculate aerosol optical thickness (AOT). Simulations showed a significant diurnal cycle of 0.2 in the dust AOT that could not be inferred from the MODIS Deep Blue retrievals due to their timings. Dust sources are mainly driven by the breakdown of the early morning low‐level jet and by moist convection in the afternoon, leading to opposite diurnal cycles. Also, simulations show that cloud cover significantly prevents the observation of AOT. The under‐sampling of the diurnal cycle by satellites plus the impact of cloud masks on the space‐borne AOT retrievals induce an underestimation of 0.28 (~40%) over the convective regions and an overestimation of 0.1 (17%) over morning source areas like Bodélé. A combination of observations and high‐resolution models could constrain bias and give a more realistic AOT climatology. Key Points: Low‐level jet and cold pool lead to opposite process‐related AOT diurnal cycles Cloud masking and temporal undersampling induce bias in satellite retrievals Combination of observations and CRM could constrain AOT bias